A new species of Caenis Stephens, 1836 (Ephemeroptera: Caenidae) from Southern Brazil - Lima, Lucas R. C.; Molineri, Carlos; Pinheiro, Ulisses (Zootaxa, 2015)
A new species of the genus Caenis Stephens is described based on the male imago, female imago and egg stages from the state of Rio Grande do Sul, Brazil. The male imago of Caenis gaucha sp. nov. is diagnosed as follows: body length of male 2.0–2.5 mm; base of antennal flagellum not dilated; forceps apically rounded, not fused to lateral margins of styliger plate; styliger plate short with posterior margin slightly sub-triangular; ratio of foreleg 1.7–2.2 × the length of hind leg, forceps length 4.4–6.0 × the width ½ from base, and distance between the extreme lateral points of the forceps bases 1.7–1.8 × forceps length.